Astronomical cycle identification and high-frequency sequence stratigraphy of the Middle Permian Lower Wuerhe Formation in the Mahu Sag, Junggar Basin - Yu, Wenhu; Yang, Guo; Liu, Jun; Yeliewubai, Shamuhaer; Yu, Jingwei (Frontiers in Earth Science, 2026)
High-resolution stratigraphic analysis is essential for reconstructing sedimentary processes and constraining reservoir architecture, yet conventional methods commonly lack quantitative time control at fourth- and fifth-order (104–105 yr) scales. Astronomical cyclostratigraphy provides a promising approach for establishing high-resolution temporal frameworks, although orbital signals in lacustrine–deltaic systems are often obscured by tectonic and autocyclic processes. This study investigates the Middle Permian Lower Wuerhe Formation in the Mahu Sag, Junggar Basin, using high-resolution gamma-ray (GR) logs and XRF-derived Fe/Ca ratios as semi-quantitative paleoenvironmental proxies. Spectral analyses (MTM, FFT), astronomical correlation tests (COCO, eCOCO), and stratigraphic tools (INPEFA, DYNOT) were integrated to identify orbital cyclicity and construct an astrochronological framework. The analyses reveal statistically significant cyclicities consistent with Milankovitch forcing, including a dominant ∼405 kyr long-eccentricity signal, subordinate ∼95–125 kyr short-eccentricity components, and higher-frequency bands tentatively interpreted as obliquity (∼36.0–44.3 kyr) and precession (∼17.8–20.8 kyr) cycles. These cycles imply an average sedimentation rate of ∼5.0–5.9 cm kyr−1. Anchored by a published zircon U–Pb age of 265.4 Ma, eleven successive 405 kyr eccentricity cycles define an astronomically calibrated duration of ∼4.45 Myr for the Lower Wuerhe Formation. Within this temporal framework, the formation is subdivided into three third-order transgressive–regressive (T–R) sequences (SQ1–SQ3) and further organized into eleven 405 kyr-paced high-frequency depositional cycles traceable across multiple wells. The results demonstrate that long-eccentricity forcing exerted a first-order control on high-frequency sedimentary cyclicity, providing a robust time-constrained basis for high-resolution stratigraphic correlation in lacustrine–deltaic systems.